SARBANES OXLEY ACT AND TAXATION: A STUDY OF THE EFFECTS ON THE TAX AGGRESSIVENESS OF BRAZILIAN FIRMS - Lopo Martinez, Antonio; Ribeiro, Alexandre Castro; Funchal, Bruno (Contabilidade Vista & Revista, 2019)
This paper investigates the effects of the Sarbanes-Oxley Act (SOX) on the tax aggressiveness of Brazilian firms that issued American Depositary Receipts (ADRs), in the period between 2004 and 2012. The aim was to investigate whether the improvement of internal controls promoted by the adoption of SOX would have any impact on the propensity to be more tax aggressive. In an environment of better internal controls, we would have more reliable information, restricting more abusive tax practices. We measured tax aggressiveness according to the effective tax rate (ETR), long-run cash effective tax rate (CASH ETR) and the difference between book income and taxable income (BTD). We compared listed Brazilian firms with ADRs (treatment group) in comparison with their peer firms only listed in Brazil, or issuers of lower level ADRs not subject to SOX (control group). The results indicate that the implementation of more stringent internal controls does not inhibit the aggressive tax practices of Brazilian firms. This study contributes to the literature on long-run tax avoidance causes and internal controls disclosures in developing countries. This research is relevant by providing some clues, in a sophisticated informational environment, the effects of a substantial improvement of internal controls would have in the tax behavior of public companies. Identifying whether, for these Brazilian companies with stock trading in the US, there would be significant modifications, after the adoption of the SOX.